The Influence of Supply Chain Strategy in Hoteling industry and Intention to Book Hotel Traveloka.com - Arissetyanto Nugroho; Molissa Dwi Zane; Janfry Sihite (International Journal of Supply Chain Management, 2020)
Abstract— The research investigates the role of of supply chain strategy in hoteling industry and intention to book hotel Traveloka.com. The questionnaire delivered to the student that is already experiencing booking hotel via Traveloka.com. The results show that the attitude positively influences the intention to book the hotel. The higher of the individual attitude toward the Traveloka.com application, the higher the intention to book the hotel online. The subjective norms which are how the normative belief of the surroundings which are the community, family friends, and social community are the references for the consumer to do or not to do an act, especially to book a hotel via the Traveloka.com application. The perception of someone or a group of people that are the reference of the consumers to use the Traveloka.com application to book a hotel is beneficial to the consumers. Moreover, the higher the support of the surrounding people to book the hotel via the Traveloka.com application, the higher the intention of the consumers to book the hotel via Traveloka.com application. The perceived behavioral control influence positively the intention to book the hotel. Therefore the higher the easiness perception and fewer obstacles, the higher the intention of the individuals to book the hotel.